Asymptotic behavior of the solutions of operators that are sum of pseudo p-Laplace type - Purbita Jana (Opuscula Mathematica, 2025)
The article investigates a Poisson-type problem for operators that are finite sum of pseudo \(p\)-Laplace-type operators within long cylindrical domains. It establishes that the rate of convergence is exponential, which is considered optimal. In addition, the study analyzes the asymptotic behavior of the related energy functional. This research contributes to a deeper understanding of the mathematical properties and asymptotic analysis of solutions in this context.